Beetles, ants, wasps, or flies? An ethnobiological study of edible insects among the Awajún Amerindians in Amazonas, Peru - Rubén Casas Reátegui; Lukas Pawera; Pablo Pedro Villegas Panduro; Zbynek Polesny (BMC, 2018)
Abstract Background Insects are known to be able to provide valuable nutrients to indigenous populations across the Amazon. However, studies on traditional insect use in the Peruvian Amazon are scarce. This study documents edible insect diversity and characterizes their food and collection patterns in eight Awajún communities in the Peruvian Amazon. Additionally, we reviewed what has been known to date about the nutrient composition of the documented species. Methods The survey was conducted among the Awajún populations living in the Huampami, Paisa, Achu, and Tseasim communities in the Cenepa district and the Shijap, San Mateo, Kusu, and Listra communities in the Imaza district. Data collection was conducted through a freelisting exercise complemented by a semi-structured inquiry form in the Awajún language. In total, 104 informants (72 men and 32 women) aged between 16 to 73 years were interviewed. Results The Awajún people use at least 12 insect species, with Rhynchophorus palmarum, Atta cephalotes, and Rhinostomus barbirostris being the most important ones. Beetles of the family Curculionidae represent the culturally most salient taxon. In the more accessible and developed Imaza district, the Awajún tend to eat almost exclusively R. palmarum, while in the more isolated and preserved Cenepa district, the community's preferences are linked with more species. Although men are the main insect collectors, women cited more edible insects on average. The insects are eaten mainly roasted or raw. Further use patterns and differences between the districts are discussed. Conclusion Traditional knowledge related to edible insects and the ecosystems they occur in is widespread among the Awajún populations, and insects still represent an important part of the indigenous food system. This ethnobiological survey discovered five species that are newly recorded as edible insects. Chemical composition of insects deemed edible by the Awajún ought to be analyzed in the future and awareness about their nutritional importance should be raised to harness the potential of this underutilized yet nutrient-rich traditional food.